Prediction of the autogenous shrinkage and microcracking of alkali-activated slag and fly ash concrete. (March 2021) - Li, Zhenming; Lu, Tianshi; Chen, Yun; Wu, Bei; Ye, Guang
Abstract: This study aims to predict the autogenous shrinkage of alkali-activated concrete (AAC) based on slag and fly ash. A variety of analytical and numerical models are available for the prediction of autogenous shrinkage of ordinary Portland cement (OPC) concrete, but these models are found to show dramatic discrepancies when applied for AAC due to the different behaviours of these two systems. In this study, a new numerical approach is developed to predict the autogenous shrinkage of alkali-activated slag (AAS) and alkali-activated slag-fly ash (AASF) concrete from the experimental results on corresponding paste. In this approach, the creep of AAS and AASF and the restraining effect of the aggregate are particularly considered. By this approach, a fairly good prediction is obtained. Moreover, the microcracking in paste caused by restraining aggregates is evaluated. The results indicate that AAC is subjected to high tendency of development of microcracking.